2013
DOI: 10.3109/15368378.2013.794734
|View full text |Cite
|
Sign up to set email alerts
|

A static magnetic field attenuates lipopolysaccharide-induced neuro-inflammatory response via IL-6-mediated pathway

Abstract: An effective method for controlling brain damage and neurodegeneration caused by inflammation remains elusive. Down-expression of the lipopolysaccharide (LPS)-induced inflammatory cytokines resulting in endotoxin tolerance is reported as an alternative anti-infection treatment. Nonetheless, because the dosage and action site are hard to control, endotoxin tolerance caused by low-dose LPS injection in brain tissue may induce side effects. The aim of this study was to test the hypothesis that static magnetic fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 52 publications
4
9
0
Order By: Relevance
“…However, an interesting observation from the present study is that body temperature does not increase in response to LPS when mice are pre-exposed to an SMF (Figure 4). Combining this observation with the findings shown in Figure 3 which demonstrate that the LPS-induced mortality rate in mice treated with SMF was significantly reduced, confirmed the results of previous reports that SMF exposure has an attenuating effect on mortality in response to LPS challenge in mice (Lin et al 2009, Shen et al 2014). Since no demonstrable effects of moderate without the LPS-challenge did not increase the thickness of the alveolar wall ( Figure 5b).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…However, an interesting observation from the present study is that body temperature does not increase in response to LPS when mice are pre-exposed to an SMF (Figure 4). Combining this observation with the findings shown in Figure 3 which demonstrate that the LPS-induced mortality rate in mice treated with SMF was significantly reduced, confirmed the results of previous reports that SMF exposure has an attenuating effect on mortality in response to LPS challenge in mice (Lin et al 2009, Shen et al 2014). Since no demonstrable effects of moderate without the LPS-challenge did not increase the thickness of the alveolar wall ( Figure 5b).…”
Section: Discussionsupporting
confidence: 94%
“…In this study, we found that SMF inhibited LPS-induced damage in the lungs, kidneys, and livers of the mice, which supports the hypothesis that SMF exposure stimulates anti-infl ammatory excitation in organs involved in MOF. Th ese fi ndings are consistent with a previous animal study which showed that SMF reduced LPS-induced mortality and cerebellar hemorrhage in mice (Shen et al 2014).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Among them, low level laser therapy (LLLT) has shown analgesic and anti‐inflammatory effects in vitro , and in vivo experimental models . Static magnetic field (SMF) therapy also has been reported to reduce inflammation and edema formation . Although the mechanism relevant to OA treatment remains unclear, the anti‐inflammation may be involved in photostimulation of LLLT and free radical reaction by SMF therapy .…”
Section: Introductionmentioning
confidence: 99%